Initiation of Early Osteoblast Differentiation Events through the Direct Transcriptional Regulation of Msx2 by FOXC1 - Mirzayans, Farideh; Lavy, Rotem; Penner-Chea, Jonathan; Berry, Fred B. (PLOS ONE, 2012)
Hierarchal transcriptional regulatory networks function to control the correct spatiotemporal patterning of the mammalian skeletal system. One such factor, the forkhead box transcription factor FOXC1 is necessary for the correct formation of the axial and craniofacial skeleton. Previous studies have demonstrated that the frontal and parietal bones of the skull fail to develop in mice deficient for Foxc1. Furthermore expression of the Msx2 homeobox gene, an essential regulator of calvarial bone development is absent in the skull mesenchymal progenitors of Foxc1 mutant mice. Thus we sought to determine whether Msx2 was a direct target of FOXC1 transcriptional regulation. Here, we demonstrate that elevated expression of FOXC1 can increase endogenous Msx2 mRNA levels. Chromatin immunoprecipitation experiments reveal that FOXC1 occupies a conserved element in the MSX2 promoter. Using a luciferase reporter assay, we demonstrate that FOXC1 can stimulate the activity of the both human and mouse MSX2 promoters. We also report that reducing FOXC1 levels by RNA interference leads to a decrease in MSX2 expression. Finally, we demonstrate that heterologous expression of Foxc1 in C2C12 cells results in elevated alkaline phosphatase activity and increased expression of Runx2 and Msx2. These data indicate that Foxc1 expression leads to a similar enhanced osteogenic differentiation phenotype as observed with Msx2 overexpression. Together these findings suggest that a Foxc1->Msx2 regulatory network functions in the initial stages of osteoblast differentiation.